Salt level for finishing swine - B A Koch; G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1975)
Two feeding trials involving 118 finishing Pigs were conducted to determine minimum salt needed in finishing diets. Performance of pigs fed 0.2 to 0.5% salt diets did not differ significantly, but pigs fed 0.1% or no salt gained significantly slower and less efficiently. Therefore, 0.2% salt in the finishing ration for swine from 100 lbs. to 215 lbs. should meet finishing pigs' requirements.; Swine Day, Manhattan, KS, November 13, 1975
Keywords: Swine day; 1975; Kansas Agricultural Experiment Station contribution; no. 505; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Salt; Finishing pigs; Performance